Superselective uterine arterial embolization with pingyangmycin-lipiodol emulsion for management of symptomatic uterine leiomyoma - 单鸿 黄明声 关守海 姜在波 朱康顺 李征然 (Chinese medical journal, 2004)
Background Uterine arterial embolization (UAE) is a safe and effective therapy for symptomatic uterine leiomyoma. This study was to assess the effectiveness and the feasibility of pingyangmycinlipiodol emulsion (PLE) for the management of symptomatic uterine leiomyoma.Methods One hundred consecutive patients (aged 21-53 years, with 38 in average ) with symptomatic uterine leiomyoma underwent superselective UAE with PLE. Clinical symptoms of the patients (including menorrhagia, bulk-related symptoms, and postprocedure-related abdominal pain) and the changes in uterine volume and tumor size after the embolization were analyzed. The patients were followed up for 8-21 months (mean, 15 months).Results Ninety-nine patients (99%,99/100) were interviewed in their first menses circle after embolization, showing improvements in their abnormal bleeding and bulk-related symptoms to some extent. Imagiological results during follow-up showed a mean of 48% reduction in uterine volume at 6 months and a mean of 75% reduction in tumor size at 9 months. Eighty-three percent of the patients reported complete resolution of postprocedure pain within 7 days.Conclusions PLE is effective in the management of uterine leiomyoma, having superiority in alleviating postprocedure-related pain.